COMBINATION OF TREMBESI (Samanea saman) ADSORBENTS AND FITORMEDIATION OF KIAMBANG (Salvinia molesta) PLANTS TO REDUCE CHROME LEVELS IN BATIK WASTE - Kurnianingtyas, Erlina (Sustainable Environmental and Optimizing Industry Journal, 2022)
Chrome (Cr) is one of the harmful heavy metals whose existence could lead to a decline in water quality, as well as harm the environment and aquatic organisms. One of the industries that generate the waste water containing chrome is the batik industry. The resulting wastewater processing needs to be done, one of which is to combine the adsorbents and trembesi seeds fitoremediasi plants Salvinia (Salvinia molesta). The purpose of this research is to know the levels of chrome on the process of adsorbsi and fitoremediasi process. This research was conducted with two processes, i.e. processes adsorbsi and fitoremediasi process. On the process of adsorbsi use two variations of the size that is the size of the mesh 30/40 mesh 60/70 and, after passing through the adsorbsi process then continues to process fitoremediasi. Treatment on the process of fitoremediasi that is the difference between living plants, IE 0-day, 2-day and 4-day. Sampling is done on each process, which is then carried out in the laboratory of environmental engineering laboratory. Based on the results of the research that has been done, the combination of adsorbent and trembesi seeds fitoremediasi plants Salvinia (Salvinia molesta) is capable of lowering the levels of chromium in waste batik. On the process of adsorbsi with 30/40 mesh size variation is obtained as a result of 8.771 mg/L and 60/70 mesh size variation of 8.092 mg/L is obtained from figure control 10.563 mg/l. To process fitoremediasi with the variation of size of mesh 30/40 adsorbent on day 0 8.730 mg/L, at 6.962 day 2 mg/L, on the 4th day of 6.212 mg/l. fitoremediasi Process with variation of the size of the mesh 60/70 adsorbent, on the 4th day 0 6.843 mg/L, on the 2nd day 5.752 mg/L, on the 4th day of 5.688 mg/L.